Geometry-based computational fluid dynamic model for predicting the biological behavior of bone tissue engineering scaffolds - Omar, Abdalla M. (2023)
The use of biocompatible and biodegradable porous scaffolds produced via additive manufacturing is one of the most common approaches in tissue engineering. The geometric design of tissue engineering scaffolds (e.g., pore size, pore shape, and pore distribution) has a significant impact on their biological behavior. Fluid flow dynamics are important for understanding blood flow through a porous structure, as they determine the transport of nutrients and oxygen to cells and the flushing of toxic waste. The aim of this study is to investigate the impact of the scaffold architecture, pore size and distribution on its biological performance using Computational Fluid Dynamics (CFD). Different blood flow velocities (BFV) induce wall shear stresses (WSS) on cells. WSS values above 30 mPa are detrimental to their growth. In this study, two scaffold designs were considered: rectangular scaffolds with uniform square pores (300, 350, and 450 µm), and anatomically designed circular scaffolds with a bone-like structure and pore size gradient (476-979 µm). The anatomically designed scaffolds provided the best fluid flow conditions, suggesting a 24.21% improvement in the biological performance compared to the rectangular scaffolds. The numerical observations are aligned with those of previously reported biological studies.